Potential ecological impacts of physical control on Spartina alterniflora in coastal wetland: Migration and transformation of nutrients and the response of bacterial community structure. (20th April 2023) - Wang, Kang; Wang, Sen; Zhang, Xin; Wang, Wenpeng; Li, Fanyi; Dong, Liu; Kong, Fanlong; Xi, Min
Abstract: The invasive species Spartina alterniflora are widely distributed on the coastline of China. In this study, three common physical control treatments for S. alterniflora were simulated in the laboratory environment. The results showed that "mowing + flooding" (MF) and "mowing + ploughing" (MP) treatments eradicated S. alterniflora completely during the 60-day experiment. However, the flooding and ploughing treatments and the decay of S. alterniflora would change the biogeochemical feature of the sediment, resulting in the abnormal release of nutrients. Spearman's correlation analysis and water quality analysis results showed that the average concentrations of NH4 + -N (1.80 mg/L) and TP (0.43 mg/L) in MF treatment, as well as NH4 + -N (1.49 mg/L), NO3 − -N (0.95 mg/L), and NO2 − -N (0.35 mg/L) in MP treatment greatly increased due to the migration and transformation of nutrient. Parallel factor analysis (PARAFAC) confirmed that three components of dissolved organic matter (DOM) and their rising in overlying water were related to the decomposition of S. alterniflora and the disturbed sediment, which could increase the risk of eutrophication in offshore water bodies. In addition, three physical control treatments changed the structure and composition of the bacterial community by altering the colonization of specific bacteria and the sediment microenvironment. Mantel test analysis and structural equation modeling (SEM) showed that the variation of key nutrients in MF and MP treatments had significant impacts on bacterial community structure. This study revealed the effects of physical control of S. alterniflora on migration and transformation mechanism of nutrients in coastal wetlands and the structure of the bacterial community. Graphical abstract: Image 1 Highlights: Physical control treatments for S. alterniflora show different ecological impacts. "Mowing + flooding" and "mowing + ploughing" may increase endogenous release risk. The persistent flooding conditions decrease bacterial richness and diversity. Decayed S. alterniflora enhances bacterial richness and diversity after ploughing.